Developmental changes in the circumsporozoite proteins of Plasmodium berghei and P. gallinaceum in their mosquito vectors - Boulanger, N.; Charoenvit, Y.; Krettli, A.; Betschart, Bruno (My University, 1995)
The circumsporozoite (CS) protein covers the surface of the sporozoite of plasmodia. Its role in the development of the malaria parasite in mosquito vectors remains unknown. CS-epitope-containing proteins appear on undifferentiated oocysts on day 7 in Plasmodium berghei and on day 5 in P. gallinaceum as demonstrated by indirect fluorescence antibody tests using monoclonal antibodies directed against the CS-protein repeats. The three-dimensional distribution of the CS-epitope-containing proteins on oocysts was analyzed by confocal scanning laser microscopy. A strong antibody binding was found in patches around the oocysts of P. berghei and P. gallinaceum, and an accumulation of labeled proteins was found at the base of the oocysts of both species. In Western blots of infected midguts and salivary glands the antibodies recognized two peptides in the salivary glands but up to ten peptides in midgut extracts. The larger number of peptides recognized in midgut preparations might indicate breakdown products during the escape of the sporozoites from the oocyst and their migration on the midgut in the mosquito vector. The data indicate a possible involvement of the CS protein in an active migration process of the sporozoites in the mosquito vector.